THE DOUNB PUBLIC LIBRARY AND ACADEMIC LIBRARIES OF DNIPRO CITY (UKRAINE) – THE PARTNERSHIP AND ITS PERSPECTIVES - Gavryliuk, Tamara M. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article analyses the benefits of professional partnership with the DOUNB public library for academic libraries in Dnipro city (Ukraine). New forms of partnership are also suggested for the future.